KARAKTERISTIK DISTRIBUSI ZAT HARA NITRAT DAN FOSFAT PADA AIR DAN SEDIMEN DI ESTUARIA TANJUNG LIMAU KOTA BONTANG KALIMANTAN TIMUR - Dimas Andika Arnando; Aditya Irawan; Lily Inderia Sari (Jurnal Tropical Aquatic Sciences, 2022)
This research was conducted in May 2021 - January 2022. The purpose of this study was to determine the distribution of nitrate and phosphate content in water and sediment in the Tanjung Limau estuary, Bontang City, East Kalimantan. Sampling of water and sediment was carried out at 4 research stations using a random method which was then analyzed at the Water Quality Laboratory and Soil Science Laboratory of PPLH Mulawarman University. The results showed that the nitrate content in the water was 0.012-0.018mg/L, 4.20-9.09% in the sediment, while the phosphate in the water was 0.014-0.077 mg/L and the phosphate in the sediment was 0.021-0.030%. The results of the analysis show that the nitrate and phosphate content is higher at Station 1 and lower towards Station 4. There is a significant difference between the nitrate and phosphate content in the water and in the sediment. The content of nitrate and phosphate is mostly sourced from upstream of the river, namely in residential areas and mangrove forests.